Strategi Sustainability Bisnis UMKM Industri Kreatif Event Organizer di Masa Pandemi Covid-19 Menggunakan Analisis SWOT-QSPM: Studi Kasus Event Organizer Prasasti Selaras di Bekasi - Dwi Irwati; Ali Mustofa; Prismawinda Anifanindi (Jurnal Maksipreneur, 2026)
This study aims to identify business strategies that the creative industry (event organizer) Prasasti Selaras must follow to maintain business stability amid significant challenges during the COVID-19 pandemic, such as market weakening and resource constraints. This research method was carried out through observation, interviews, and brainstorming with the Prasasti Selaras expert to identify the internal factors (strengths and weaknesses) and external factors (opportunities and threats) affecting the Prasasti Selaras event organizer business. The SWOT analysis approach and the Quantitative Strategic Planning Matrix (QSPM) are used to identify strategies for maximizing opportunities and minimizing weaknesses to anticipate threats. The results of the study show that the position of the Prasasti Selaras is in Cell IV, which means the organization is in a good position to grow and develop. Several strategic priorities that can be used as alternative strategies for Prasasti Selaras to maintain business stability are innovating new products, creating online events as an alternative, and collaborating with external HR with an open management system.